Isolation and identification of Legionella spp. from nonhospital facilities: a preliminary one-year surveillance study in the urban area of Pesaro-Urbino (Central Italy) - Sabatini, L.; Sisti, M.; Campana, R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Legionella is considered one of the most important causes of potentially preventable morbidity and mortality. These microorganisms are ubiquitous, but incomplete information is available on the geographic distribution of Legionella species in our region.Study design. For the mentioned reasons, in this work the distribution of Legionella spp. in non-hospital facilities of the urban area of Pesaro-Urbino (Central Italy), including public fountains, residential buildings, public and private offices and retirement homes, was investigated.Methods. A total of 298 water samples were collected from the different facilities and subjected to standard Legionella isolation and identification protocols.Results. As reported, 17.8% of the collected water samples resulted positive for Legionella spp. (28.6% from retirement homes, 21.3% from residential buildings, 15.3% from private and public offices). The highest percentage of positive samples (14.4%) was found in hot water from retirements homes (58.8%) and residential buildings (31.8%); the most frequent isolated serogroups were L. pneumophila 2-14 (71.7%).Conclusions. This work is the first describing the distribution of Legionella spp. in non-hospital facilities in the province of Pesaro-Urbino, and highlights a condition of potential risk for susceptible categories. From our data, we can point that a regular and constant control to prevent microbiological risk from legionellosis, particularly in facilities housing the elderly, is recommended.